INJUSTICE IN EKA KURNIWAN’S NOVEL BEAUTY IS A WOUND - Fatmaliza Harahap; Asnani Asnani (Universitas Islam Sumatera Utara, 2023)
This study entitled Injustice in Eka Kurniawan’s Novel Beauty is a Wound focuses on the injustice experienced by some women, Dewi Ayu and her four daughters. The main purpose of this study is to determine the types of injustice experienced by some women. In analyzing the novel Beauty is a Wound, descriptive research method was used to identify, classify and analyze the data. The collected data are divided into two categories: primary data and secondary data. The primary data is the novel Beauty is a Wound (2002) itself. The secondary data are some books and literatures related to the analysis such as from books or journals of injustice issues, from the internet and other relevant information to the analysis. The data are collected through library research. The result of the study shows that there are three types of injustice found in the novel. They are discrimination, subordination and violence.